An Analysis Of Hasan Hanafi's Occidentalism: Dismantling Western Epistemological Hegemony For Non-Western Knowledge - Lukman; Wawan Sopiyan (El-Ghiroh : Jurnal Studi Keislaman, 2025)
This study examines the construction of occidentalism within the framework of contemporary Islamic theology, focusing on Hasan Hanafi's thought and its contribution to maintaining epistemology in the non-Western world. The aim of the study is to identify the forms of occidentalism that emerge in contemporary Islamic theological discourse. It explores Hasan Hanafi's approach to the deconstruction of Western epistemology and assesses the impact of Hanafi's thought on the development of knowledge discourse in non-Western contexts. The methods used are critical library research and hermeneutic textual analysis of Hasan Hanafi's main works, as well as a comparative study of the literature on occidentalism and epistemology in non-Western regions. The results show that Hasan Hanafi offers a systematic critique of the pretensions of universality of Western epistemology with an emphasis on epistemic plurality, the historical reconstruction of Muslim experience, and the need for an autonomous normative basis for knowledge production in the Islamic world. His thought challenges the tradition-modernity dichotomy and introduces the concept of cultural reconstruction as a strategy to restore the epistemic heritage of non-Western societies. The study concludes that Hasan Hanafi's contribution enriches contemporary Islamic theological discourse by offering a critical epistemic framework that rejects occidentalist domination and opens up space for pluralistic dialogue between local traditions and intellectual innovation.